2023
DOI: 10.3390/tropicalmed8020112
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Leptospirosis Infection Severity

Abstract: Background: Leptospirosis is an important health problem in Thailand. People infected with leptospirosis may not have any mild symptoms, whereas some people have acute and severe illnesses. It is crucial to strengthen critical patients’ diagnosis and treatment to prevent severe complications and reduce mortality. This study was performed to explore a set of parameters for the prediction of severe leptospirosis illness under routine clinical practice. Methods: A case-control study was conducted in eight general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Climate is known to have influence on the distribution of human pathogens [28]. Thailand is predominantly an agricultural country, locates in a tropical zone, which has a hot and humid climate with different epidemiology from other countries [29]. Meanwhile, it is one of the most visited countries globally, improving opportunities for pathogens transmission all around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Climate is known to have influence on the distribution of human pathogens [28]. Thailand is predominantly an agricultural country, locates in a tropical zone, which has a hot and humid climate with different epidemiology from other countries [29]. Meanwhile, it is one of the most visited countries globally, improving opportunities for pathogens transmission all around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies about the clinical factors associated with severe leptospirosis have shown signs and symptoms like hemorrhage [ 33 ], pulmonary signs and symptoms (abnormal lung sounds, dyspnea) [ 33 ], hypotension, oliguria, jaundice [ 52 , 53 ], and hyperkalemia [ 33 ]. Laboratory testing as packed cell volume (PCV: 29.8%), hyponatremia (<131 mEq/L), and highest alanine transaminase (ALT: 70 IU/L) were found to be independently associated with severe disease [ 52 , 54 ]. We found rash, dyspnea, tachycardia, and jaundice associated with severe leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a review estimated that 11–53% of dengue virus infections present rash compared to 5% of leptospirosis cases [ 58 ]. Studies in Puerto Rico [ 59 ], Thailand [ 52 ], and Nicaragua [ 38 ] did not find evidence that rash was an indicator of severe or fatal leptospirosis. In India, one study found that skin rash was significantly associated with leptospirosis in children [ 60 ], and another study found only suggestive evidence of such an association among urban leptospirosis cases [ 61 ], but not a sign of severity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be pulmonary involvement, and this is described as severe pulmonary hemorrhage syndrome, which reaches a fatality rate greater than 50% [7]. The prognosis depends on early diagnosis, severity, and timely intensive treatment [8]. However, the presentation is usually different in different geographical areas of the world and is explained by variations in intrinsic virulence between serovars and existing species [4].…”
Section: Introductionmentioning
confidence: 99%